STRATEGI KOMUNIKASI EKSTERNAL DALAM MENINGKATKAN PENJUALAN PADA PT MAYORA INDAH TBK: STUDI KASUS PT K33 DIVISI MARKETING YOGYAKARTA - Nafiah, Daimatun; Ramadhan, Muhammad Rizki (PARADIGMA: Jurnal Ilmu Administrasi, 2025)
This study aims to describe the external communication strategy in increasing sales at PT Mayora Indah Tbk, with a case study of PT K33 Marketing Division Yogyakarta. The research uses a qualitative descriptive method with a case study approach. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model: data reduction, data display, and conclusion drawing. The results show that the external communication strategies include direct promotion to consumers, maintaining relationships with business partners, and sponsoring major events. The media used include print, electronic/digital, and audio-visual platforms. Challenges faced include limited branding in remote areas, suboptimal media use, lack of internal team knowledge, market competition, and changing consumer preferences. Solutions implemented include forming field teams, developing internal applications, conducting product knowledge training, offering attractive promotions, and continuous market research.